Program Magang pada Divisi Finance & Accounting PT Olsera Indonesia Pratama - Wisnu Yuwono; Shelby Esfandiany (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Digitalization has become a key driver in enhancing the competitiveness and operational efficiency of MSMEs. PT Olsera Indonesia Pratama, through its Point of Sale (POS) application, is committed to supporting the digital transformation of MSMEs in Indonesia. However, a significant challenge was identified in the settlement process, which was time-consuming and inefficient. This study aims to design a solution to accelerate and improve the accuracy of the settlement process. Methods included interviews with Olsera's Finance & Accounting team and direct observation of back-office workflows. The implemented solution involved creating a merchant database, developing automated Excel templates, and providing user guidelines. As a result, the settlement process time was reduced from several days to just 3 hours, with significant improvements in data accuracy and operational efficiency.